Semiotika Komunikasi Politik: Analisis Dimensi Sintaktik, Semantiks, dan Pragmatiks Charles William Morris pada Logo PDI Perjuangan - Nizar Zulmi Ramadhan; Erika Sherren Darma; Moh. Dey Prayogo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the symbolic meaning of the Indonesian Democratic Party of Struggle (PDI Perjuangan) logo through the syntactic, semantic, and pragmatic dimensions of Charles William Morris's semiotic theory. The study employed a descriptive qualitative approach using semiotic analysis of the official logo, the party's Constitution and Bylaws (AD/ART), and related party documents. The findings indicate that, syntactically, the logo possesses a well-organized, contrasting, and easily recognizable visual structure. Semantically, the bull's head, the red, black, and white colors, and the circular shape represent nationalism, Marhaenism, courage, consistency, integrity, and unity. Pragmatically, the logo functions as a political identity, a communication medium, a tool for strengthening the party's image, and an instrument for fostering constituent loyalty across various communication platforms. The integration of these three dimensions demonstrates that the PDI Perjuangan logo constitutes a sign system that effectively connects visual structure, ideological values, and political communication functions within Indonesia's political landscape.